PENENTUAN HYDRAULIC CONDUCTIVITY TANAH PASIR BERLANAU KONDISI JENUH DAN JENUH SEBAGIAN BERDASARKAN PENGEMBANGAN ALAT - , HERDY SETIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
post-rain puddles problem that occurs in The First Yard of Prambanan Temple is caused by soil characteristics changes when the post-quake restoration was being done in 2006. Thus an instrument and method which capable to effectively measure field soil characteristics, especially hydraulic conductivity from unsaturated to saturated condition is highly needed. In this research, there are two developed instrument and procedure to measure field hydraulic conductivity, the immediate flow and constant flow method. Immediate flow method used a test tube filled with water until certain height. Afterwards, the time period of water level changes were being counted. Constant flow method used a test tube filled with constant water flow until the height remains at a particular position. Both methods were carried out from unsaturated to saturated condition. Decagon Devices were used to measure volumetric water content variance during testing. Based on the results, hydraulic conductivity relation to volumetric water content variance was obtained by using numerical approach. ï±r parameter used in VG model calculation can be determined by testing or modeling. The results showed that ï±r obtained from very dry soil conditions had the optimum value. Hydraulic conductivity range value with a density of 2.04 gr/cm3 for unsaturated condition is 4 x 10-6 cm/sec (Sr= 83%) to 1 x 10-5 cm/sec (Sr = 95%). The developed equipment that was being used for this test was sufficiently effective to measure in situ hydraulic conductivity in silty sand soil without using Soil Water Characteristic Curve which is quite expensive. Keywords: puddles, developed in situ measurement, hydraulic conductivity, silty sand soil.